TWO OBSTACLES TO ENABLING CHANGE IN ELF-AWARE TEACHER EDUCATION AND HOW TO OVERCOME THEM - Sifakis, Nicos C. (Estudos Linguísticos e Literários, 2020)
In this paper I discuss the possibilities, opportunities, challenges and (even) perils in applying the ELF-aware perspective in teacher education. I focus on presenting two obstacles in enabling this application, the first related to teachers’ attitudes, which tend to be fundamentally negative, and the second referring to an uncertainty about establishing, applying and evaluating appropriate ELF pedagogy. The obstacles are discussed with reference to examples from my personal experience as teacher educator, and argue (a) that these obstacles are also present in more “traditional” teaching and teacher education practices and (b) that they can be overcome if they are perceived as opportunities for integrating real-life interactions involving non-native English language users in the EFL classroom and prompting EFL teacher reflection and growth.